2017
DOI: 10.1080/15592324.2017.1290040
|View full text |Cite
|
Sign up to set email alerts
|

Plant “electrome” can be pushed toward a self-organized critical state by external cues: Evidences from a study with soybean seedlings subject to different environmental conditions

Abstract: In the present study, we have investigated how the low-voltage electrical signals of soybean seedlings change their temporal dynamic under different environmental conditions (cold, low light, and low osmotic potential). We have used electrophytografic technique (EPG) with sub-dermal electrodes inserted in 15-days-old seedlings located between root and shoot, accounting for a significant part of the individual seedlings. Herein, to work on a specific framework to settle this type of the study, we are adopting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 31 publications
2
69
0
3
Order By: Relevance
“…However, further exploration demands extreme (stable) experimental conditions (especially temperature) and even more sophisticated measuring devices (an 8½-digit voltmeter), which were beyond our reach. Only then, can an important subject concerning external, environmental cues at the organism level (Souza et al 2017) and many others that are mentioned here be properly addressed. Moreover, all future experiments should be performed with caution (Yakushenko et al 2014) to avoid any artefacts that might originate from the chemistry of the nanoparticles that are used in the solute-semiconductor interface.…”
Section: Discussionmentioning
confidence: 99%
“…However, further exploration demands extreme (stable) experimental conditions (especially temperature) and even more sophisticated measuring devices (an 8½-digit voltmeter), which were beyond our reach. Only then, can an important subject concerning external, environmental cues at the organism level (Souza et al 2017) and many others that are mentioned here be properly addressed. Moreover, all future experiments should be performed with caution (Yakushenko et al 2014) to avoid any artefacts that might originate from the chemistry of the nanoparticles that are used in the solute-semiconductor interface.…”
Section: Discussionmentioning
confidence: 99%
“…All datasets used herein to test the different methods of classification are part of the study published by Souza et al (2017). The data consist of time series of low-voltage variation ( V Δ in μV ) measured in soybean plants subjected to different environmental stimuli: cold, low light and osmotic stress.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…For instance, Sukhov et al (2014) and Magdalena et al (2017) have demonstrated the role of electrical signals in the regulation of photosynthetic responses to different stimuli. Very recently, Souza et al (2017) proposed the concept of "plant electrome" based on the general proposition of "electrome" by De Loof (De Loof, 2016), describing the totality of the ionic currents in different scales of plant organization. By measuring low-voltage electrical signal using eletrophytography (EPG) (Debono, 2013;Souza et al, 2017), Souza et al (2017) showed that different environmental stimuli could change some characteristics of the temporal dynamic of the electrical signaling, including the level of complexity.…”
mentioning
confidence: 99%
See 2 more Smart Citations